Communication in Africa: the importance of the word - Stiegler, Karen (1993)
Communication in Africa: the importance of the word It is impossible to talk about communication in Africa without first locating this element in a historical, social, cultural and economic context: The first thing that must be clear is that Africa is not a monolithic and homogeneous whole, but a continent with 55 countries and extremely diverse culture . In other words, the cultures existing in Africa can be diverse, even opposed to one another. Another aspect that should be noted is that communication is global in Africa: it is linked to music, instruments, the human body, etc. It is also linked to history, the past, the present and the future.